A survey of experimental research on contests, all-pay auctions and tournaments - Emmanuel Dechenaux; Dan Kovenock; Roman M. Sheremeta (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
Many economic, political and social environments can be described as contests in which agents exert costly efforts while competing over the distribution of a scarce resource. These environments have been studied using Tullock contests, all-pay auctions and rankorder tournaments. This survey provides a review of experimental research on these three canonical contests. First, we review studies investigating the basic structure of contests, including the contest success function, number of players and prizes, spillovers and externalities, heterogeneity, and incomplete information. Second, we discuss dynamic contests and multi-battle contests. Then we review research on sabotage, feedback, bias, collusion, alliances, and contests between groups, as well as real-effort and field experiments. Finally, we discuss applications of contests to the study of legal systems, political competition, war, conflict avoidance, sales, and charities, and suggest directions for future research.
Keywords: C7; C9; D7; H4; J4; J7; K4; L2; M5; 330; contests; all-pay auctions; tournaments; experiments